Immunology for pharmacy - Flaherty, Dennis K., 1944- (Elsevier/Mosby, 2012)
With a new pharmacy-specific approach to immunology, Immunology for Pharmacy prepares pharmacists for practice by providing a complete understanding of the basis of immunology and the consequences of either suppressing or enhancing immune function. It covers key subjects such as prophylaxis and vaccination, antibodies as therapeutic and diagnostic agents, biological modifiers, and the rationale for use and mechanisms of therapeutic agents. Written by experienced author and educator Dennis Flaherty, this book presents topics with a logical, step-by-step approach, explaining concepts and their practical application. A companion Evolve website reinforces your understanding with flashcards and animations. Pharmacy-specific coverage narrows the broad field of immunology to those areas most pertinent and clinically relevant to pharmacy students. 165 full-color illustrations help to illuminate difficult concepts. Factors That Influence the Immune Response chapter covers biological agents including bacteria, viruses, and fungi, and their related toxins and how they relate to the immune system. Three chapters on vaccinations prepare you for this important part of the pharmacist's role by discussing cancer treatment with whole tumor vaccines, cell vaccines, and viral vector vaccines, describing other vaccines such as recombinant vaccines and plant vaccines, and examining how diseases such as diphtheria, whooping cough, and tetanus respond to vaccinations. A summary of drugs used in treating each condition helps you understand typical treatments and their immunological mechanisms, so you can choose proper treatments. Integrated information makes it easier to understand how various parts of the immune system work together, leading to a better understanding of immunology as a whole. A unique focus on practical application and critical thinking shows the interrelationship of concepts and makes it easier to apply theory to practice. Information on AIDS covers the identification and treatment of both strains of HIV as well as AIDS, preparing you for diseases you will see in practice. Unique student-friendly features simplify your study with learning objectives and key terms at the beginning of each chapter, bulleted summaries and self-assessment questions at the end of each chapter, and a glossary at the back of the book. Over 60 tables summarize and provide quick reference to important material. A companion Evolve website includes animations and pharmacy terminology flashcards.- Resumé vydavatel
Keywords: imunologie; imunofarmakologie; immunology; immunopharmacology; elektronické knihy; sborníky; electronic books; papers of several authors